Sociological-Normative Analysis of The Provision of Joint Property in The Cyber Era - Musarrofa, Ita; Nisak, Sofiatun; Muzakki, Mochammad Rofyal; Rachman, Aulia Avan (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2022)
Economic activity in the information technology era does not only occur in the real world but also in cyberspace. There are so many things that can be done in cyberspace that can bring economic benefits, for example ownership of a youtube channel, web hosting, google adsense, crypto and so on. This fact raises the problem of joint property in the family. Can the acquisition of property through the economic activity of husband and wife in cyberspace during the marriage period be included as joint property that must be divided when the marriage breaks up? This problem needs to be studied sociologically and normatively. This sociological study is intended to find an explanation of how the process of creating economic institutions in cyberspace uses Michael Heim's theory of the characteristics of cyberspace and Peter L. Berger's dialectical theory of society formation. Normatively, the problem of joint property in the cyber era is analyzed using Islamic legal norms, positive law, and customary law. The data is taken from searching documents on the internet and other documents such as journals and books that discuss human activities in the cyber era. These data were then analyzed using the sociological and normative perspectives above. Sociologically, the character of the cyber world in the form of simulation, interaction, artificiality, immersion, telepresence, and networked communications makes people choose economic activities using the internet, because of the convenience it provides. This activity occurs through a dialectical process of externalization, objectivation and internalization that makes the cyber world economic order sustainable. Normatively, the assets produced by a husband and/or wife through their economic activities in the cyber world during a marriage can be included in the category of joint property which must be divided in two when the marriage breaks up.